A Qualitative Exploration of Triangulated Shared Decision Making in Rheumatoid Arthritis - Binder-Finnema, Pauline (Arthritis Care Res (Hoboken), 2019)
OBJECTIVE: Treat-to-target implementation in rheumatoid arthritis (RA) requires a shared decision making (SDM) process. However, ability to pay is a major determinant of patient choice, but how this factor affects SDM is under explored. METHODS: Visits at four RA clinics during which patients faced a decision to change their treatment were audiotaped between May 2016 and June 2017. Audiotapes were transcribed verbatim and analyzed using qualitative Framework Analysis. RESULTS: 156 visits were analyzed. Most RA patients, except those with effective insurance coverage, had deliberations disrupted or sidelined by third-party insurance providers having power to authorize the preferred DMARD choice. This triangulated SDM complicated efficiency in deliberations and timely treatment, and was a barrier to shared engagement about health risks and symptom improvement typically found in patient-provider dyads. CONCLUSION: Rheumatology care providers should aim to incorporate treatment costs and ability to pay into their deliberations so individualized out-of-pocket estimates can be considered during triangulated SDM at point-of-care.